Consumer reactions to corporate social responsibility brands: the role of face concern. Issue 1 (11th January 2016) - Wan, Lisa C.; Poon, Patrick S.; Yu, Chunling
Abstract : Purpose: – Face concern is a personal value that refers to the extent an individual shows regard for or interest in the protection and enhancement of face. This study aims to examine the moderating influence of face concern on consumer responses to brands associated with corporate social responsibility (CSR). Design/methodology/approach: – An experimental study was conducted to test the proposed conceptual model in consumer reactions to CSR brands. Findings: – The results show that consumers with a high face concern (vs low face concern) have a better quality perception toward CSR brands than non-CSR brands. In addition, they also have a higher purchase intention and propensity to recommend the CSR brands than those with a low face concern. However, this interaction effect between face concern and brand type (CSR brand vs non-CSR brand) is mediated by consumers' perceived quality of the brand. Practical implications: – This study provides critical implications for the formulation of brand management strategies, particularly for international firms entering an Asian country like China where people generally have a high degree of face concern. Originality/value: – This study highlights the moderating role of face concern in the relationship between consumer responses and brands associated with CSR. It also suggests the mediating role of consumers' perceived brand quality in the relationship between brand types (CSR brands vs non-CSR brands) and consumer responses.